Peran Kyai dalam Membina Keharmonisan Keluarga Pondok Pesantren - Zainul Arifin; Haderi; Taufik (ASA, 2021)
The kiai is the central figure in the Islamic boarding school and has its own characteristics compared to other educational figures. In developing Islamic boarding schools, of course, the kiai has a strategy that is adapted to his capacity, such as the development of strategies for increasing human resources in outer and inner independence to lead families, students and communities.The purpose of this study is to describe the role of the kyai as a leader in managing the dynamics of family harmony (Household, Santri and Community) in the Islamic boarding school environment.This study uses a descriptive qualitative approach. By case study type. Data collection techniques in this study were in-depth interviews, observation, and documentation. The data analysis uses data condensation, data presentation, and drawing conclusions.The role of the Kyai is to use his function properly to provide mutual benefits to others, where as religious leaders often provide religious teachings and lectures so that it is possible for a kyai to become the center of attention and be used as a role model by the family of alumni students and the community. Kyai's steps in fostering family harmony in Islamic boarding schools have varied ways of giving their roles. To develop leadership integrity in the community, their families and students, they must have a strategy, namely respecting family, friends or other people, building trust between individuals and creating harmony, strengthening shared values. create a communication that has a certain pride and find the basics of common ground.